Tetradentate Pt(II) Complexes Based on Xylenylamino Linked Dual Pyrazolate Chelates for Organic Light Emitting Diodes - Zhou, Fan; Pan, Yi; Hung, Wen‐Yi; Chen, Ching‐Feng; Chen, Kui‐Ming; Li, Jian‐Liang; Yiu, Shek‐Man; Liu, Yi‐Mei; Chou, Pi‐Tai; Chi, Yun; Lau, Kai‐Chung (Chemistry : a European journal, 2024)
In this work, we report the syntheses of three Pt(II) emitters, namely, Pt4N1, Pt4N2, and Pt4N3, to which their tetradentate chelates were assembled by linking two pyrazolate chelates with a single xylenylamino entity. Functionalization of Pt4N1 was achieved upon the addition of electronegative CF3 substituent on pyridinyl groups and switching to more electron‐deficient pyrazinyl groups in giving Pt4N2 and Pt4N3, respectively. The vertically arranged xylenylamino entity has effectively suppressed the inter‐molecular π‐π stacking and Pt⋅⋅⋅Pt interaction, as shown by the single crystal X‐ray structural analyses. Upon fabrication of OLED devices, Pt4N2 and Pt4N3 based devices delivered efficient cyan and green emission, with an EQEmax of 15.2 % and 11.2 %, respectively, affirming the successfulness of the tetradentate chelating strategy. Functional tetradentate chelates composed of two pyrazolate chelates and one xylenylamino linker were employed in preparation of Pt(II) complexes showing efficient ligand‐centered ππ* transition characteristics. Upon fabrication of OLED devices, Pt4N2 and Pt4N3 based devices delivered efficient cyan and green emission, with an EQEmax of 15.2 % and 11.2 %, respectively, affirming the successfulness of the tetradentate chelating strategy.